Investigating Islamic Education Teachers as Role Models in Character Formation and Professional Ethics - Annisaul Khairat; Marjoni Imamora Ali Umar; Iskandar Fuaddin; Luqyana Mardhiyah; Yarhamna (Research Journal on Teacher Professional Development, 2026)
Teachers' professional ethics have long been recognized as a cornerstone of character education; however, empirical evidence explaining how Islamic Education (PAI) teachers enact ethical professionalism as role models in shaping primary school students' character remains limited. This study explores the role of PAI teachers as ethical role models and examines the factors that support and constrain the enactment of professional ethics in primary school settings. Employing a qualitative case study design, the research was conducted across several primary schools, with PAI teachers serving as the primary participants. Data were collected through in-depth interviews, classroom observations, and document analysis and analyzed using an iterative thematic approach. The findings demonstrate that teachers' ethical professionalism, reflected in honesty, fairness, discipline, empathy, and consistency between words and actions, plays a central role in facilitating the internalization of students' character values through everyday classroom interactions and school culture. Nevertheless, the enactment of these ethical practices is constrained by excessive administrative responsibilities, limited opportunities for continuous professional development, and insufficient value-based supervisory mechanisms. These findings suggest that strengthening teachers' professional ethics requires not only individual commitment but also institutional support that integrates professional learning, ethical leadership, and reflective supervision. The study contributes to the growing literature on teacher professionalism by demonstrating that ethical role modelling constitutes a fundamental mechanism through which character education is translated into authentic educational practice in primary schools.